Eksplorasi Konsep Pembinaan Masyarakat Islam melalui Tradisi khataman Al-Quran di Masjid Agung Lamongan dan Masjid Namira - Ulya, Musrifatul (Fakultas Dakwah UIN KHAS Jember, 2023)
The Quran is the holy book of Islam, making it of paramount importance in the global Muslim faith. Memorization and comprehension of the Quran are significant traditions, such as the khataman. Gratitude rituals, like